Forest Resources Dependency of the Rural Community: A Case Study in Bokeo Province, Lao Pdr - Somsoulivong, Bounmy (2002)
This study used the Rural Survey Technique (RST) to examine the socioeconomic aspect of the rural community in Bokeo Province, Laos, in order to assess the contribution of forest resources to the rural community household's economy, and address the problems related to the forest dependency. This study has identified factors that contributed to the forest dependency of the rural people. An estimation of the quantity and monetary value of various timber and non-timber forest products (TFPs & NTFPs), collected from the forest and the products cultivated and harvested from forestlands (CFLPs), annually utilized by the rural community, has been made as well as the rural household's income derived from these products. Descriptive statistics has been applied to describe and summarize the data to envisage the overall forest dependency of the rural community. The statistical techniques such as T- test; and A NOVA have been used to analyze the data. The multiple regression analysis was also applied to develop a forest dependency model for 12 studied villages in the Nam Nhou and Nam Choam areas, Bokeo province, Lao PDR. The regression model was developed incorporating five socio-economic variables.